Normative Values of Financial Stability Ratios: Industry-Specific Features - E. A. Fedorova; M. A. Chukhlantseva; D. V. Chekrizov (Управленческие науки)
The purpose of this study is to predict the Russian companies’ bankruptcy probability based on existing legislation. The empirical base of the study consists of the collection of financial statements of 2017 enterprises (866 of them gone bankrupt) belonging to four economic sectors: wholesale trade, construction, power generation, food production. In the course of investigation the authors have examined the consistency of current normative values of financial ratios approved by the regulatory acts of the Russian Federation, as well as proposed their redefined data based on economic and mathematic modeling. The worked out norms of financial stability allow classifying companies with sufficient accuracy as bankrupts and financially healthy companies (from 75% to 85%). The given norms have been calculated for two groups of insolvent companies: 1) formally declared bankrupts; 2) officially declared bankrupts and the companies, which are the stage of the arbitration proceedings according to creditors’ claims. The obtained results can be applied in enterprises’ crisis management decision-making.